Studi Viabilitas pada Pasien yang Tidak Dapat Menghentikan Nitrat Long-acting - Erwin A Soeriadi; Badai B Tiksnadi; Junan Imaniar; Hendra Budiawan; A Hussein S Kartamihardja (Universitas Kristen Maranatha, 2021)
The information of myocardial viability status is important to decide the management of CAD. Myocardial viability study (VS) with short-acting nitrate (SAN)-added is recommended to perform inpatient with CAD before revascularization therapy. This study aims to determine whether there are differences in the perfusion results of myocardial viability studies with Long-acting nitrate (LAN) and those with added SAN. Three patients with CAD were referred to our department for myocardial VS to determine the treatment choice. Long-acting nitrate (LAN) was consumed regularly every day and not allowed to be stopped due to the symptomatic chest pain. Patients underwent two myocardial perfusion VS, the first study with continuing the daily routine LAN only and the second one with SAN-added to the daily routine LAN. VS was analyzed qualitatively. The result of this study, no significant perfusion difference between LAN treatment only and SAN-added studies, it is possible the LAN regular dose alone is sufficient to create a vasodilating effect on the arteries without the need for addition of SAN. Conclusion, patients who take LAN routinely, VS might be performed without the need to take additional vasodilator prior to radiopharmaceutical injection.Keywords: coronary artery disease; myocardial perfusion imaging; revascularization therapy; viability study